Physiological Profiling and Microorganism Community Analysis of Cirebon Shrimp Paste Fermentation â€œTerasiâ€ using BIOLOGTM EcoPlate (Indonesian Society for microbiology, 2018)
Terasi or shrimp paste is an Indonesian traditional seasoning made from fermented small shrimp or krill. Different indigenous microorganism community exhibit different physiological function due to lack standard in its materials and processing. This study aimed to determine physiological profiles and microorganism community in Cirebon shrimp paste fermentation. BIOLOGTM EcoPlate was used to obtain microbial physiological function of the krill and 2-months old shrimp paste. Microorganisms were later isolated from EcoPlate substrate to determine its community structure. Average Well Color Development (AWCD) from krill was thirty times higher than shrimp paste. Interestingly, this study revealed a shift of carbon source utilization at day-28 of fermentation from amino acid and polymer to phenolic compound. In addition, AWCD index increased in accordance with increased of microorganism community complexity at day-28. Within 56 days of fermentation there was a slightly increase in water, fat, and carbohydrate content. In contrast, there was decrease in protein, ash content, and acidity level from neutral to acid, with salinity level resulted in between 16.26% to 21.42%. We conclude that there is a change of microorganism community within shrimp paste fermentation corresponding to metabolism activity which affects the product quality.Â